Paranasal Sinuses Anatomy and Conditions - Singh Gendeh, Balwant (IntechOpen, 2022)
This book discusses selected topics on the anatomy of paranasal sinuses and related conditions, providing insight into advancements in the field. The first section covers morphological aspects of the maxillary sinus, infectious causes of acute and chronic sinusitis, posterior ethmoidal artery, and paranasal sinuses anatomy and anatomical variations. The second section covers sinonasal-associated midfacial expansion and maxillary sinus in dental implantology. Chapters present new clinical and research developments as well as future perspectives on ever-expanding upper airway and jaw problems.